Editors’ Introduction: Legitimacy, Recognition, and Everyday Judgment in Asian Societies - Asep Muhamad Iqbal (Journal of Asian Social Science Research, 2023)
Abstract This editors’ introduction presents JASSR Vol. 5, No. 2 (2023) as an inquiry into legitimacy, recognition, and everyday judgment in Asian societies. The issue brings together studies on populist party politics in India and Japan, Indonesia’s Chinese minority, public perceptions of Rodrigo Duterte’s leadership in the Philippines, customer satisfaction models in e-commerce, women’s education under the Taliban, and Qur’anic family life in Afghanistan. Together, the articles show how power becomes credible, contested, or morally judged in concrete social settings. The issue highlights the value of Asian social science that connects institutions, markets, families, public debates, and lived experience.